EVALUASI KINERJA PELAYANAN PUBLIK - Ali Yusri, Raja Juarisman, Harapan Tua, R.F.S, (Jurnal Ilmu Administrasi Negara, 2020)
Evaluate the performance of public services. The purpose of this study was to evaluate the performance of public services in the Regional Technical Implementation Unit of the Drinking Water Supply System (UPTD SPAM) of Siak Regency, and analyze the factors that hampered the public service performance of the Siak Regency UPTD SPAM. The study uses descriptive qualitative research methods, data collection techniques through interviews, observation and documentation. The results showed that the performance of the Siam District UPTD was not optimal and needed to be improved. Plan evaluation, performance process evaluation, performance measurement evaluation, evaluation of goals and objectives and evaluation of public service outcomes are still low. Human resource factors, budgetary and financial management factors, infrastructure factors, and work motivation factors influence or even hinder the performance of public services.